The chemistry of protactinium—VII The fluoro-complexes - Bukhsh, M. N.; Flegenheimer, Juan; Hall, F. M.; Maddock, A. G.; Ferreira de Miranda, C. (Northern Ireland, 1966)
Fil: Flegenheimer, Juan Comisión Nacional de Energía Atómica; Argentina